Development of a Didactical Design Based on Research and Development for Teaching Cones and Cylinders to Improve Junior High School Students’ Conceptual Understanding - Husna, Nurul; Nurhasanah, Nurhasanah (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to develop a didactical design based on Research and Development to improve junior high school students’ conceptual understanding of cones and cylinders by addressing their learning obstacles through structured instructional materials. Methodology: This study employed a Research and Development approach adapted from Borg and Gall and Sugiyono models. The research involved eighth-grade students, using interviews, observation sheets, validation instruments, and questionnaires. Data were analyzed using descriptive qualitative and quantitative methods with Likert scale scoring. Expert validation involved mathematics education lecturers and teachers. Small-scale and large-scale trials were conducted to evaluate the developed module’s feasibility and effectiveness in mathematics learning on cones and cylinders. Main Findings: The developed didactical design module showed significant improvement after expert validation and revision. The results indicated very good criteria in content quality, language clarity, and media design. Student responses in small-scale and large-scale trials reached 90–94%, categorized as very good. The module effectively reduced learning obstacles and improved students’ conceptual understanding of cones and cylinders. The findings confirm that the instructional material is valid, practical, and effective for classroom implementation. Novelty/Originality of this study: This study develops a didactical design module integrating learning obstacle analysis specifically for cones and cylinders using an R&D approach. The innovation lies in its structured adaptation of students’ cognitive difficulties into instructional design. It contributes a context-specific mathematics learning module that enhances conceptual understanding and provides a practical model for developing geometry-based teaching materials.